2021
DOI: 10.1158/2159-8290.cd-21-1004
|View full text |Cite
|
Sign up to set email alerts
|

Firefighters for the Wrong Type of Inflammation in Tumors

Abstract: Summary: In this issue of Cancer Discovery, Pelly and colleagues show that inhibition of prostaglandin E2 synthesis or its activity on EP2 and EP4 receptors synergizes with anti–PD-1 immunotherapy and triggers a potent intratumoral IFNγ response in mouse models and in fresh surgical human tumor explants. This therapeutic strategy is in line with other interventions that aim at fostering immunotherapy by means of quenching protumor inflammation. See related article by Pelly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The clinical significance of this may extend to cytotoxic T-cell function within the TME, which is critical for ICI efficacy. Prior studies have shown that cytokines such as IL-1β, TNFα, and IL-6/IL-6R promote inflammation that is damaging to cytotoxic T lymphocyte immunity ( 91 94 ). In our study, these cytokines were notably up-regulated by treatment with ICI alone, in contrast to treatment with EC5026 alone or in combination with ICI.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of this may extend to cytotoxic T-cell function within the TME, which is critical for ICI efficacy. Prior studies have shown that cytokines such as IL-1β, TNFα, and IL-6/IL-6R promote inflammation that is damaging to cytotoxic T lymphocyte immunity ( 91 94 ). In our study, these cytokines were notably up-regulated by treatment with ICI alone, in contrast to treatment with EC5026 alone or in combination with ICI.…”
Section: Discussionmentioning
confidence: 99%
“…olid tumors can be understood as abnormal organs with a microenvironment populated by transformed cancer cells and normal immune and stromal cells [1]. Understanding how the composition of this complex microenvironment relates to tumor status or progression is the key to personalized anticancer therapies [2]. This requires answering questions such as: which cell phenotypes populate the tumor or the stromal compartment?…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the ongoing CANOPY-A and CANOPY-N (159,161) are evaluating canakinumab in the adjuvant and neoadjuvant settings in surgically amenable cases, respectively. Reasons for failure may indicate that more than one redundant pro-inflammatory mechanism may be at play in latestage cancer and combined inhibition may be (162).…”
Section: Il-1 and Il-1mentioning
confidence: 99%